Invariant Natural Killer T Cells As Suppressors of Graft-versus-Host Disease in Allogeneic Hematopoietic Stem Cell Transplantation - Mavers, Melissa; Maas-Bauer, Kristina; Negrin, Robert S. (Frontiers in Immunology, 2017)
Invariant natural killer T (iNKT) cells serve as a bridge between innate and adaptive immunity and have been shown to play an important role in immune regulation, defense against pathogens, and cancer immunity. Recent data also suggests that this compartment of the immune system plays a significant role in reducing graft-versus-host disease (GVHD) in the setting of allogeneic hematopoietic stem cell transplantation. Murine studies have shown that boosting iNKT numbers through certain conditioning regimens or adoptive transfer leads to suppression of acute or chronic GVHD. Preclinical work reveals that iNKT cells exert their suppressive function by expanding regulatory T cells in vivo, though the exact mechanism by which this occurs has yet to be fully elucidated. Human studies have demonstrated that a higher number of iNKT cells in the graft or in the peripheral blood of the recipient post-transplantation is associated with a reduction in GVHD risk, importantly without a loss of graft-versus-tumor effect. In two separate analyses of many immune cell subsets in allogeneic grafts, iNKT cell dose was the only parameter associated with a significant improvement in GVHD or in GVHD-free progression-free survival. Failure to reconstitute iNKT cells following allogeneic transplantation has also been associated with an increased risk of relapse. These data demonstrate that iNKT cells hold promise for future clinical application in the prevention of GVHD in allogeneic stem cell transplantation and warrant further study of the immunoregulatory functions of iNKT cells in this setting.